The transformation of economic analysis at the federal reserve during the 1960s - Juan Acosta; Beatrice Cherrier (Duke University, Center for the History of Political Economy (CHOPE), 2019)
In this paper, we build on data on Fed officials, oral history repositories, and hitherto under-researched archival sources to unpack the torturous path toward crafting an institutional and intellectual space for postwar economic analysis within the Federal Reserve. We show that growing attention to new macroeconomic research was a reaction to both mounting external criticisms against the Fed's decision making process and a process internal to the discipline whereby institutionalism was displaced by neoclassical theory and econometrics. We argue that the rise of the number of PhD economists working at the Fed is a symptom rather than a cause of this transformation. Key to our story are a handful of economists from the Board of Governors' Division of Research and Statistics (DRS) who paradoxically did not always held a PhD but envisioned their role as going beyond mere data accumulation and got involved in large-scale macroeconometric model building. We conclude that the divide between PhD and non-PhD economists may not be fully relevant to understand both the shift in the type of economics practiced at the Fed and the uses of this knowledge in the decision making-process. Equally important was the rift between different styles of economic analysis.
Keywords: 330